Unintended pregnancy and antenatal care behavior in Indonesia - Lorensia Panselina Widowati; Rita Damayanti (Alma Ata University Press, 2022)
Background: One in four mothers experience unwanted pregnancy. It causes great risks for mothers and children, such as malnutrition, neglected, violence and even death. During pregnancy, a woman is expected to take the initiative and change her behavior by taking adequate care. Antenatal care is a part of maternal and child health services that are vital in early detection and monitoring of fetal well-being as an efforts to improve the health of mothers and babies during pregnancy, childbirth and postpartum. The mother's intention towards her pregnancy, whether desired or not, is related to the mother's behavior during pregnancy. Unintended pregnancy can obstruct the achievement of adequate antenatal care..Objectives: This study aims to determine the relationship between unintended pregnancy and antenatal care behaviorMethods: This study used a cross-sectional design with the secondary data from 2017 Indonesian Demographic Health Survey. The dependent variable in this study was antenatal care behavior which is a composite of the first antenatal visit, frequency of antenatal visit and iron consumption. There were 14.223 women of childbearing age 15-49 years which eligible for this study’s criteria. The collected data was analyzed with chi square and logistic regression models of risk factors testResults: Mothers with unintended pregnancies have a bigger opportunity to do unhealthy antenatal care behavior (OR = 2.338: 95% CI 1.707- 3.203) compared to intended pregnancies. The effect of unintended pregnancy on antenatal care behavior varies according to maternal age (OR- 1.267: 95% CI 1.034-1.553), parity (OR= 0.579: 95% CI 0.430-0.780) and residency (OR= 1.490: 95% CI 1.226- 1.811).Conclusions: There is a relationship between unintended pregnancy and antenatal care behavior. Mothers with unintended pregnancies is 2.338 times more likely to have unhealthy antenatal behavior care. We also found that this effect differs according to the maternal age, parity and residency.